2011
DOI: 10.1177/0267659111408379
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde autologous priming reduces transfusion requirements in coronary artery bypass surgery

Abstract: The hypothesis was tested whether retrograde autologous priming (RAP) of the cardiopulmonary bypass system, compared to a standard primed system (NON-RAP group), results in less haemodilution and less transfusion of packed red blood cells. Retrospectively, data was collected from the medical charts of one hundred patients undergoing elective coronary artery bypass grafting using cardiopulmonary bypass. Fifty patients where RAP was used have been compared to fifty patients using NON-RAP. The prime volume in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 21 publications
3
31
0
2
Order By: Relevance
“…1 As a result of lowered perioperative hematocrit negatively influencing both cerebral autoregulation and postoperative neurologic outcome, low hematocrit levels due to excessive hemodilution should be avoided, and techniques limiting hemodilution could prove beneficial. 18,19 The arterial CO 2 level has been demonstrated to affect cerebral blood flow by altering cerebral vasomotor reactivity. 20 The authors' data also show that ARI decreases with increasing p a CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…1 As a result of lowered perioperative hematocrit negatively influencing both cerebral autoregulation and postoperative neurologic outcome, low hematocrit levels due to excessive hemodilution should be avoided, and techniques limiting hemodilution could prove beneficial. 18,19 The arterial CO 2 level has been demonstrated to affect cerebral blood flow by altering cerebral vasomotor reactivity. 20 The authors' data also show that ARI decreases with increasing p a CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In a comparable study performed by Stalder et al, prevention of intraoperative excessive hemodilution led to a decrease in transfusion rates [21]. Ševerdija et al used retrograde autologous priming method, obtained more than 2-fold gain in prime volumes, and demonstrated that use of this method increased intraoperative hematocrit values and also decreased requirement for transfusion [22]. In the present study, group in whom integrated arterial filters were used, a prime volume of 1450 cc was used, while in the nonintegrated group a prime volume of 1650 cc was used.…”
Section: Discussionmentioning
confidence: 99%
“…7 Treatment for intraoperative anaemia often involves the administration of PRBC, a practice which is associated with adverse outcomes of its own. 2,3 Recognising the detrimental effects of haemodilution has led to various innovative techniques for its avoidance, such as autologous priming, [8][9][10][11] vacuum-assisted venous drainage with smaller diameter venous lines 12 and the development of mini extracorporeal circuits. 13 Using a smaller oxygenator is a simple and effective method for reducing haemodilution, particularly in smaller patients.…”
Section: Discussionmentioning
confidence: 99%